Cultural Influences on Problem Solving and Decision-Making in Student Projects: A Comparative Study between Indonesia and Germany - Achmad, Fandi; Febriyani, Widia; Nzefa, Raoul; Ahkim, Fadma; Rania, Attouk (Metris: Jurnal Sains dan Teknologi, 2024)
Differences in cultural dimensions across countries can influence approaches and behavior patterns in education. Therefore, this study aims to analyze the influence of culture on problem-solving and decision-making in student projects in Indonesia and Germany. A comparative approach between the two countries identifies significant cultural differences in power distance, individualism, masculinity, uncertainty avoidance, long-term orientation, and indulgence. The research method used is a qualitative approach with descriptive analysis. Data was collected through interviews and observations of students involved in the project. The study results show that cultural differences affect students' approaches to problem-solving and decision-making. In Indonesia, group cooperation and conformity to social norms play an important role, while independence and critical thinking are prioritized in Germany. The implications of this research are the importance of increasing cultural awareness, developing collaborative skills, increasing independence and critical thinking, and empowering students with cultural knowledge. By understanding cultural differences and taking the right steps, educators can create an inclusive learning environment and prepare students to face the challenges of an increasingly globalized world.